2017
DOI: 10.1002/ange.201701796
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Aminothiolation of 1,3‐Dienes via a Dihydrothiazine Intermediate

Abstract: Heteroatom-containing organic molecules are of particular interest to medicinal chemists and materials scientists.Astrategy to reach these architectures via direct difunctionalization of abundant 1,3-dienes is especially attractive. Herein, we describe the development of ar egio-and diastereoselective 1,4-aminothiolation of 1,3-dienes with as ulfur diimide reagent, acopper catalyst, and alkylGrignardreagents. This unique protocol provides remote nitrogen and sulfur functionalities with high levels of stereocon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We observed that the reaction with benzenethiol, 2 a did not produce the targeted product 6 while reacting with pyrrolidine, the aminated product 7 was formed with 90% yield. With these convincing results, we were interested to perform another reaction by taking the aminated product (7) reacting with benzenethiol, 2 a under the standard condition and interestingly, the desired thioaminated product 4 a was obtained with 81% yield (Scheme 2c). However, the reaction with diphenyl disulfide (8) under the same reaction condition produced no desired product 4 a (Scheme 2d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the reaction with benzenethiol, 2 a did not produce the targeted product 6 while reacting with pyrrolidine, the aminated product 7 was formed with 90% yield. With these convincing results, we were interested to perform another reaction by taking the aminated product (7) reacting with benzenethiol, 2 a under the standard condition and interestingly, the desired thioaminated product 4 a was obtained with 81% yield (Scheme 2c). However, the reaction with diphenyl disulfide (8) under the same reaction condition produced no desired product 4 a (Scheme 2d).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] According to the recent literature, the construction of CÀ N and CÀ S bond has been achieved through the direct thioamination of alkene, alkyne and aryne systems. [6][7][8][9][10][11][12] In this context, unsaturated dione-based organic molecules have come into consideration in the periphery of the difunctionalization reaction. Particularly, 1,4-naphthoquinones have been utilized for difunctionalization by oxidative coupling with anilines and sulfonyl azide considering only a single CÀ H bond to participate.…”
Section: Introductionmentioning
confidence: 99%